Analisis Perbandingan Kompresi File Audio Menggunakan Algoritma Shannon Fano Dengan Algoritma Fibonacci Code - Simanjuntak, Sari Magdalena (Jurnal Kajian Ilmiah Teknologi Informasi dan Komputer, 2023)
Compression is a technique used to reduce the size of the data that serves to reduce memory capacity and speed up the data transfer process. In this study, the method used is the Shannon Fano method and the Fibonacci Code. In the Shannon Fano method the compression process is carried out by knowing the frequency of occurrence of each symbol which will then be sorted from the largest to the smallest frequency, while the Fibonacci Code method uses the Fibonacci integer series to encode the bit value of the data or file to be compressed. The file to be compressed is an audio file with an MP3 extension, to perform compression in reducing the size of the audio file, the technique used is lossless. Lossless technique is a compression technique that can restore compressed files converted to their original form (decompression). The algorithms used in file compression both use lossless techniques. Files that have been compressed using the Shannon Fano and Fibonacci Code methods will be compared to find out which method is more efficient in compressing audio files. The results showed that the method of Shannon Fano and Fibonacci can compress audio files. Based on the analysis of the compression ratio results generated using the Shannon Fano algorithm, there was a 69% change using 48 data samples, while the compression ratio results generated using the Fibonacci algorithm experienced a 66% change using the same 48 data samples as the Shannon Fano algorithm